NAVIGATING THE FUTURE OF NATURE SCHOOLS: TRENDS, PROSPECTS, AND HURDLES - Diani, Rahma; Diana, Nirva; Saregar, Antomi; Putra, Fredi Ganda; Fitri, Megawati Ridwan (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The development of the learning concept is not always discussed in the classroom. The application of this concept can be found in the nature school. This study aimed to find out the trends, opportunities, and challenges of the nature school. The research method employed was a systematic literature review with steps referring to the Durst & Edvardsson 2012 guidelines. The Scopus database in the last five years was used as the research data with three main keywords: Nature School, Forest School, and Eco-school. The search found 25 articles that matched the topic of the nature school, which were then analyzed. The results showed that the themes raised in the 25 articles positively impacted students, green environmental issues, teacher leadership in nature schools, and nature school practices. The research themes rarely discussed were teacher leadership and the issue of the nature school environment. This gap served as an excellent opportunity for researchers to research the themes.